Utilization of Antiviral Medications in COVID-19 Patients with Chronic Kidney Disease in Hospital - Saristiana, Yuneka; Prasetyawan, Fendy; Muslikh, Faisal Akhmal; Dhafin, Anis Akhwan; Mildawati, Ratna; Putri, Elsa Mahardika; Raharjo, Susilo Margining (PT FORMOSA CENDEKIA GLOBAL, 2023)
The COVID-19 pandemic has presented a substantial global health challenge, affecting diverse patient populations, particularly those with chronic kidney disease. Hospitals are presently dependent on two antiviral medications, favipiravir and remdesivir, to mitigate the impact of this disease on patients with chronic kidney disease. This study aims to evaluate the utilization of favipiravir and remdesivir in COVID-19 patients with chronic kidney disease in a hospital setting. This research will employ a retrospective approach to gather data from the medical records of COVID-19 patients with chronic kidney disease who received treatment with favipiravir or remdesivir in the hospital. Considering the prevalence of favipiravir usage at 64% and remdesivir at 36%, this research aims to provide a comprehensive understanding of the effectiveness and associated risks of toxicity linked to these two medications in COVID-19 patients with chronic kidney disease